Lithium supplement agent and preparation method thereof, positive pole piece and secondary battery

By forming an iron boride cladding on the surface of lithium phosphite, the existing lithium supplement material is solved, and the battery energy density and cycling performance are achieved, and the cost is reduced.

CN119725489APending Publication Date: 2025-03-28HUBEI WANRUN NEW ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411978505.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The lithium supplementary materials of existing lithium-ion batteries have problems such as poor safety, stability and high cost.

Method used

Lithium phosphite is used as the lithium supplement agent, and a cladding layer composed of iron boride material is formed on its surface. The safety performance and stability of lithium phosphite are improved through this cladding layer.

Benefits of technology

It improves the safety performance and stability of lithium supplements, reduces preparation costs, and enhances the energy density and circulation performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725489A_ABST
    Figure CN119725489A_ABST
Patent Text Reader

Abstract

The invention provides a lithium supplement agent, and belongs to the technical field of energy storage, the lithium supplement agent comprises lithium phosphite and a coating layer coating the surface of the lithium phosphite; and the material of the coating layer comprises iron boride. According to the invention, the problems of poor safety and stability, high cost, residues in the lithium supplementing process and the like of the lithium supplementing material in the related technology can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage technology, and in particular to a lithium supplement and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art

[0002] Lithium-ion batteries are widely used in energy storage fields such as new energy vehicle batteries. Lithium-ion batteries have become one of the most widely used secondary batteries in the fields of new energy vehicles, due to their advantages such as high theoretical capacity, stable operating voltage, high energy density, long cycle life, and good chemical stability.

[0003] During the first charge of a lithium-ion battery, a solid electrolyte interphase (SEI) film will form on the surface of the negative electrode of the battery, consuming a large amount of active lithium, causing irreversible lithium loss, resulting in a decrease in the energy density and cycle performance of the lithium-ion battery, limiting the application of lithium-ion batteries. Based on this problem, pre-lithiation or lithium supplementation is usually used to compensate for the loss of active lithium, thereby improving the energy density and cycle stability of lithium-ion batteries.

[0004] Compared with negative electrode lithium replenishment, positive electrode lithium replenishment has attracted much attention due to its easier operation and better safety. However, most of the current lithium replenishment materials with high lithium capacity are prone to produce gas during the first charging process, which can easily cause the battery volume to expand, thereby causing battery safety and stability issues. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application provides a lithium supplement agent and a preparation method thereof, a positive electrode plate and a secondary battery, aiming to solve the problems of poor safety and stability and high cost of lithium supplement materials in the related technology.

[0006] In a first aspect, an embodiment of the present application provides a lithium supplement, comprising: lithium phosphite and a coating layer coated on the surface of the lithium phosphite;

[0007] Wherein, the material of the coating layer includes iron boride.

[0008] In the technical solution of the embodiment of the present application, in the lithium supplement agent, a coating layer having iron boride is used to coat the surface of the lithium phosphite. On the one hand, after the lithium is removed, the lithium phosphite will obtain two lithiums and metaphosphoric acid, and will not generate waste gas, which is beneficial to improving the safety performance; on the other hand, the lithium phosphite is coated with the coating layer, and the lithium phosphite is not easy to contact with the external environment, which is beneficial to avoid the oxidation of phosphite to phosphate, thereby reducing the formation of "dead lithium" and improving the lithium supplement effect. Even if a small amount of lithium phosphite leaks, it will react to form salt due to the residual alkali on the surface of the lithium supplement agent, avoiding the The lithium supplement agent is corroded, thereby improving the stability of the lithium supplement agent; on the other hand, the metaphosphoric acid generated after lithium phosphite is de-lithiated has strong water absorption, so the product after lithium phosphite is de-lithiated can absorb a small amount of water in the lithium supplement agent, which is beneficial to avoid water entering the electrolyte and causing the decomposition of the electrolyte, and further improve the performance stability of the lithium supplement agent and the battery; finally, the lithium phosphite is coated with a coating layer having iron boride. Since the material of the coating layer has strong stability and good conductivity, the stability of the lithium supplement agent is improved while the conductivity of the lithium supplement agent is improved. In addition, compared with the high lithium capacity lithium supplement material such as lithium-rich lithium ferrite used in the related art, the raw material price of the lithium supplement agent is low and the cost is low.

[0009] In some embodiments, the coating layer has a thickness of 0.6 μm to 2 μm, and / or a coating rate of the coating layer is greater than or equal to 93%.

[0010] In this embodiment, the thickness and coverage rate of the coating layer are controlled within the above range, which is beneficial for the coating layer to more completely cover the lithium phosphite, reduce the leakage of lithium phosphite, and avoid the coating layer hindering the lithium ion conduction of the lithium phosphite.

[0011] In some embodiments, the lithium phosphite is spherical, and the sphericity of the spherical shape is 0.81-0.87; and / or the particle size distribution of the lithium supplement agent satisfies: D50 particle size is 0.3 μm-3.8 μm, D10 particle size is 0.1 μm-1.9 μm, and D90 particle size is 1.3 μm-6.4 μm.

[0012] In this embodiment, controlling the sphericity of the lithium supplement agent within the above range is beneficial to adjusting the sphericity of the lithium phosphite, so that the coating layer can more easily completely coat the lithium phosphite; and the particle size distribution of the lithium supplement agent satisfies: when the D50 particle size is 0.3μm ~3.8μm, the D10 particle size is 0.1μm ~1.9μm, and the D90 particle size is 1.3μm ~6.4μm, the particle size distribution of the lithium supplement agent is concentrated and the particle size is small, which can effectively reduce the granularity during the coating process when applied to the positive electrode sheet, thereby improving the flatness of the positive electrode sheet.

[0013] In some embodiments, the tap density of the lithium supplement agent is 1.43 g / mL to 1.59 g / mL; and / or, the compacted density of the lithium supplement agent is 2.48 g / mL to 2.76 g / mL; and / or, the specific surface area of ​​the lithium supplement agent is 3.47 m 2 / g~4.79 m 2 / g.

[0014] In this embodiment, controlling the tap density and compaction density of the lithium supplement agent within the above range is beneficial to effectively improving the energy density of the lithium supplement agent; controlling the specific surface area of ​​the lithium supplement agent within the above range is beneficial for the lithium supplement agent to have a suitable contact area with the electrolyte when used in a secondary battery, thereby giving full play to the lithium supplement effect.

[0015] In a second aspect, the present application provides a method for preparing a lithium supplement, comprising:

[0016] providing a first slurry, the first slurry comprising lithium phosphite;

[0017] The first slurry is mixed with sodium borohydride and ferrous chloride, and subjected to a first reaction treatment to obtain a crude product;

[0018] The crude product is filtered, washed and dried to obtain the lithium supplement agent;

[0019] Wherein, the lithium supplement comprises lithium phosphite and a coating layer coated on the surface of the lithium phosphite, and the material of the coating layer comprises iron boride.

[0020] In the technical solution of the embodiment of the present application, after preparing the slurry of lithium phosphite, the slurry of lithium phosphite is mixed with sodium borohydride and ferrous chloride, and the sodium borohydride and ferrous chloride react to obtain ferric boride, thereby obtaining a lithium supplement agent having an ferric boride coating layer formed on the surface of the lithium phosphite. In the lithium supplement agent, on the one hand, after lithium removal, the lithium phosphite will obtain two lithiums and metaphosphoric acid, and will not generate waste gas, which is beneficial to improving safety performance; on the other hand, the lithium phosphite is coated with a coating layer, and the lithium phosphite is not easy to contact with the external environment, which is beneficial to avoid the oxidation of phosphite to phosphate, thereby reducing the formation of "dead lithium" and improving the lithium supplement effect. Even if a small amount of lithium phosphite leaks, The residual alkali Li2O on the surface of the lithium supplement will also react to generate salts, thus preventing the lithium supplement from being corroded, thereby improving the stability of the lithium supplement. On the other hand, the metaphosphoric acid generated after lithium phosphite is de-lithiated has strong water absorption, so the product after lithium phosphite is de-lithiated can absorb a small amount of water in the lithium supplement, thereby preventing the water from entering the electrolyte and causing the decomposition of the electrolyte, further improving the performance stability of the lithium supplement and the battery. Finally, the lithium phosphite is coated with a coating layer having iron boride. Since the material of the coating layer has strong stability and good electrical conductivity, the conductivity of the lithium supplement is improved while improving the stability of the lithium supplement. In addition, compared with the high lithium capacity lithium supplement materials such as lithium-rich lithium ferrite used in the related art, the raw materials of the lithium supplement are cheap and the preparation cost is low.

[0021] In some embodiments, providing a first slurry, the first slurry comprising lithium phosphite, comprises:

[0022] obtaining a first solution of phosphorous acid, wherein the solvent of the first solution comprises at least one of methanol, ethanol, glycerol, propanol and propylene glycol;

[0023] Adding lithium salt to the first phosphorous acid solution, performing a second reaction treatment, and obtaining a first reaction slurry;

[0024] The first reaction slurry is ground until the lithium phosphite in the first reaction slurry reaches a preset particle size to obtain a first slurry.

[0025] In this embodiment, lithium salt is added to the first solution of phosphorous acid, and lithium phosphite is crystallized from the first solution by a second reaction treatment and utilizing the low solubility of lithium phosphite in the above solvent, so as to obtain a first reaction slurry, and then the lithium phosphite in the first reaction slurry is ground to a preset particle size by grinding the first reaction slurry, thereby obtaining a first slurry. Among them, using phosphorous acid as a raw material is conducive to keeping the first slurry acidic, so that when the first reaction treatment is subsequently performed, the first reaction treatment is maintained under acidic conditions, which is conducive to the generation of iron boride, and the iron boride is chemically plated on the surface of lithium phosphite to form a coating layer.

[0026] In some embodiments, the molar ratio of phosphorous acid, sodium borohydride and ferrous chloride is 1:(0.05-0.1):(0.025-0.05); and / or,

[0027] The temperature of the second reaction treatment is 35°C to 55°C, and the time of the second reaction treatment is 0.5 h to 1 h; and / or,

[0028] The lithium salt comprises: at least one of lithium carbonate, lithium sulfite and lithium bicarbonate; and / or,

[0029] The molar ratio of lithium element in the lithium salt to phosphorous acid is (1.8-1.9):1; and / or,

[0030] The preset particle size is 0.3μm~3μm.

[0031] In this embodiment, the ratio of the amount of phosphorous acid, sodium borohydride and ferrous chloride is controlled within the above range, so that the first reaction treatment is carried out under acidic conditions and an excess of sodium borohydride, which is conducive to the reaction of sodium borohydride and ferrous chloride, and the formation of a coating layer of suitable thickness on the surface of lithium phosphite. By controlling the temperature and time of the second reaction treatment within the above range, it is conducive to the reaction of lithium salt and phosphorous acid to generate lithium phosphite to be fully carried out. By using lithium carbonate, lithium sulfite and / or lithium bicarbonate, these lithium salts react with phosphorous acid to generate lithium phosphite and gas, thereby reducing the introduction of impurities while preparing lithium phosphite. By controlling the ratio of the amount of lithium element in the lithium salt to phosphorous acid to (1.8~1.9): 1, phosphorous acid is appropriately excessive, which is conducive to maintaining acidic conditions and facilitating the first reaction treatment to be carried out under acidic conditions. By controlling the preset particle size to 0.3μm~3μm, it is conducive to obtaining lithium phosphite with a concentrated particle size distribution and a small particle size, which is conducive to the coating of the coating layer and obtaining a lithium supplement with a concentrated particle size distribution and a small particle size.

[0032] In some embodiments, the step of mixing the first slurry with sodium borohydride and ferrous chloride and subjecting the mixture to a first reaction treatment to obtain a crude product comprises:

[0033] After mixing a solution containing sodium borohydride, a solution containing ferrous chloride and the first slurry, a crude product is obtained at a first reaction temperature and after a first preset time.

[0034] In this embodiment, after a solution containing sodium borohydride and a solution containing ferrous chloride are mixed with the first slurry, the mixture is subjected to a first preset time at a first reaction temperature to facilitate a full reaction of sodium borohydride and ferrous chloride, and the reaction product is used to uniformly coat the lithium phosphite, thereby improving the uniformity of the coating layer in the crude product.

[0035] In some embodiments, the mixing time is 60 min to 120 min, and the mixing temperature is 25° C. to 45° C.; and / or,

[0036] The temperature of the first reaction treatment is 25°C to 45°C; and / or,

[0037] The first preset time is 30 min~60 min.

[0038] In this embodiment, by controlling the mixing time and temperature, the uniformity of the mixing of the first slurry with sodium borohydride and ferrous chloride can be improved, so as to facilitate the full coating of lithium phosphite. By controlling the first reaction temperature to be 25°C to 45°C, and / or the first preset time to be 30min to 60min, it is conducive to fully generating iron boride and coating the surface of lithium phosphite, and then it is conducive to forming a coating layer with a suitable thickness and coverage on the surface of lithium phosphite. At the same time, by controlling the mixing temperature to be the same as the temperature of the first reaction treatment, iron boride can be generated during the mixing process, which is conducive to the full generation of iron boride, and is conducive to improving the coating uniformity of the coating layer and improving the coverage.

[0039] In some embodiments, the temperature of the drying process is 80° C. to 100° C., and the vacuum degree of the drying process is -0.09 MPa to -0.07 MPa.

[0040] In this embodiment, by controlling the temperature and vacuum degree of the drying process, the introduction of oxygen and water vapor in the air is reduced, which is beneficial to improving the material stability of the lithium supplement and reducing the generation of by-products such as lithium phosphate.

[0041] In a third aspect, an embodiment of the present application provides a positive electrode plate, including a current collector, and a positive electrode material arranged on at least one side of the current collector along its thickness direction, wherein the positive electrode material includes the lithium supplement agent as described in the first aspect or a lithium supplement agent prepared by the preparation method of the lithium supplement agent as described in the second aspect.

[0042] In this embodiment, the positive electrode plate includes the above-mentioned lithium replenisher, which adopts a coating layer having iron boride and is coated on the surface of lithium phosphite. It has improved safety performance, stability, conductivity and lithium replenishment effect and low cost, thereby improving the safety, stability, conductivity and lithium replenishment effect of the positive electrode plate and reducing the cost of the positive electrode plate, and is beneficial to increasing the capacity of the battery when applied to the battery.

[0043] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator; wherein the positive electrode sheet is selected from the positive electrode sheet described in the third aspect.

[0044] In this embodiment, the secondary battery includes the above-mentioned positive electrode sheet, and thus has the advantages of the positive electrode sheet.

[0045] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0047] Figure 1 A schematic diagram of a process for preparing a lithium supplement provided in an embodiment of the present application;

[0048] Figure 2 This is a scanning electron microscope result image of the lithium supplement provided in Example 1 of the present application;

[0049] Figure 3 This is a graph showing the particle size distribution results of the lithium supplement provided in Example 1 of the present application. DETAILED DESCRIPTION

[0050] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0052] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0053] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0054] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0055] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0056] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.

[0057] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0058] At present, the common positive electrode lithium supplement materials with high lithium capacity mainly include lithium-rich compounds (such as lithium-rich lithium iron oxide (Li5FeO4), lithium-rich lithium nickel oxide (Li2NiO2), etc.) and binary lithium compounds (such as Li3N, Li2O2, etc.). Among them, lithium-rich compounds have poor air stability, easy water absorption and hydrolysis, and gas production (oxygen, etc.). In addition, lithium-rich compounds are sensitive to water vapor and carbon dioxide in the air, and are prone to react to generate surface residual alkali, which makes homogenization difficult and hinders the migration of lithium ions. At the same time, lithium-rich compounds also have problems such as poor air stability and high prices. In addition, lithium-rich compounds need to use lithium oxide as raw material, which has high alkalinity and is difficult to process. In the process of lithium supplementation, a large amount of oxygen will be released and LiFeO2 will remain, which will have a certain impact on the performance of the battery cell. Binary lithium compounds have a higher voltage platform, and oxygen will be released during the first charge and react with the electrolyte, destroying the stable SEI film between the positive electrode and the electrolyte, thereby worsening the stability of the battery and even causing safety problems.

[0059] Therefore, how to provide a lithium supplement with higher safety, higher stability and lower cost has become an urgent problem to be solved.

[0060] In order to solve the above technical problems, the embodiments of the present application provide a lithium supplement agent and a preparation method thereof, a positive electrode plate and a secondary battery. The lithium supplement agent provided in the embodiments of the present application has the advantages of good stability, high safety, low cost and good lithium supplement effect. When applied to the positive electrode plate of the battery, it is beneficial to effectively improve the coulombic efficiency of the positive electrode material and compensate for the loss of lithium at the negative electrode caused by the formation of the SEI film, thereby helping to improve the capacity and cycle performance of the secondary battery with the lithium supplement agent; and thus the electrochemical performance of the positive electrode plate and the secondary battery is also improved.

[0061] The electric device provided in the embodiment of the present application may be, but is not limited to, a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.

[0062] In a first aspect, an embodiment of the present application provides a lithium supplement, which includes: lithium phosphite and a coating layer coated on the surface of the lithium phosphite, wherein the material of the coating layer includes iron boride.

[0063] In the lithium replenishment process of the lithium replenisher, on the one hand, after lithium is removed from the lithium phosphite, two lithiums and metaphosphoric acid will be obtained, and no waste gas will be generated, thereby improving the safety performance of the lithium replenisher. On the other hand, the lithium phosphite is coated with a coating layer, and the lithium phosphite is not easy to contact with the external environment, which reduces the oxidation of phosphite to phosphate, thereby reducing the formation of "dead lithium" and improving the lithium replenishment effect. At the same time, even if a small amount of lithium phosphite leaks out, it will react to form salts due to the residual alkali (such as Li2O, etc.) on the surface of the lithium replenisher, thereby preventing the lithium replenisher from being corroded, thereby improving the stability of the lithium replenisher. On the other hand, the metaphosphoric acid generated after lithium phosphite is removed from the lithium has strong water absorption. Therefore, the product after the lithium phosphite is removed from the lithium can absorb a small amount of water in the lithium replenisher, which is beneficial to prevent water from entering the electrolyte and causing the decomposition of the electrolyte, and further improve the performance stability of the lithium replenisher and the battery.

[0064] Furthermore, the lithium phosphite is coated with a coating layer having iron boride. Since the material of the coating layer has strong stability and good conductivity, the stability of the lithium supplement is improved while the conductivity of the lithium supplement is improved. In addition, the strong stability and good stability of iron boride are conducive to its role as a conductive agent in the positive electrode sheet.

[0065] Furthermore, compared with the high lithium capacity lithium supplement material such as lithium-rich lithium ferrite used in the related art, the raw material price of the lithium supplement is low, which effectively reduces the preparation cost of the lithium supplement.

[0066] Specifically, when the lithium supplement agent is applied to the positive electrode material, the lithium phosphite in the lithium supplement agent is used to supplement lithium. After lithium removal, two lithiums and metaphosphoric acid (the reaction equation is shown in the following formula (1)) will be obtained, and no waste gas will be generated, which is beneficial to improving safety performance. At the same time, by using a coating layer to coat the lithium phosphite, the lithium phosphite is not easy to leak out. Even if a small amount of lithium phosphite leaks out, it will react to form salts due to the alkalinity of the residual alkali on the surface of the lithium supplement agent (the reaction equations are shown in the following formulas (2) and (3)), which is beneficial to avoiding the lithium supplement agent from being corroded and improving the stability of the lithium supplement agent. Furthermore, since metaphosphoric acid has strong water absorption, it can absorb a small amount of water in the lithium supplement agent (the reaction equation is shown in the following formula (2)), which is beneficial to avoiding water from entering the electrolyte and causing the decomposition of the electrolyte. Furthermore, coating the lithium phosphite with a coating layer is beneficial to preventing the phosphite from being oxidized to phosphate, and the material of the coating layer has strong stability and good conductivity, which improves the stability of the lithium supplement while improving the conductivity of the lithium supplement.

[0067] Li2HPO3→2Li+2HPO3 Formula (1);

[0068] HPO3+H2O→H3PO4 formula (2);

[0069] Li2O+2H3PO4→2LiH2PO4+H2O formula (3).

[0070] In some embodiments, the coating layer may have a thickness of 0.6 μm to 2 μm. Preferably, the coating layer may have a thickness of 1 μm to 2 μm. For example, the coating layer may have a thickness of 0.63 μm, 0.67 μm, 1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2 μm.

[0071] In these embodiments, the thickness of the coating layer is controlled within the above range, which is beneficial for the coating layer to more completely cover the lithium phosphite, reduce the leakage of lithium phosphite, and avoid the coating layer hindering the lithium ion conduction of the lithium phosphite.

[0072] In some embodiments, the material of the coating layer is iron boride.

[0073] In some embodiments, the coating rate in the coating layer is greater than or equal to 93%. The coating rate refers to the percentage of the coverage area of ​​the coating layer on the surface of the lithium phosphite to the total surface area of ​​the lithium phosphite. Preferably, the coating rate in the coating layer is 93% to 99%. More preferably, the coating rate in the coating layer is 94% to 99%. For example, the coating rate of the coating layer can be 95%, 96%, 97%, 98%, 99% or 100%. The coating layer can completely coat the lithium phosphite, reduce the leakage of lithium phosphite and reduce the contact of lithium phosphite with the external environment, which is conducive to improving the lithium supplement effect.

[0074] In some embodiments, the surface of lithium phosphite is relatively smooth, which is conducive to the coating layer to more completely coat the lithium phosphite.

[0075] In some embodiments, the lithium supplement is spherical, and the sphericity of the lithium supplement is greater than 0.8. For example, the sphericity of the lithium supplement may be 0.81, 0.82, 0.83, 0.84, 0.85, 0.9, 0.92, 0.94, 0.95 or 0.99.

[0076] In some embodiments, the lithium supplement has a sphericity of 0.81 to 0.87. For example, the sphericity of the spherical shape can be 0.81, 0.82, 0.83, 0.84, 0.85, 0.86 or 0.87.

[0077] In some embodiments, the particle size spacing of the lithium supplement agent (i.e., the value of (D90 particle size-D10 particle size) / D50 particle size) is 0.7-4, and the particle size distribution of the lithium supplement agent is concentrated, which is beneficial to reduce the granularity when the lithium supplement agent is applied to the positive electrode sheet, thereby improving the flatness of the positive electrode sheet.

[0078] In some embodiments, the particle size distribution of the lithium supplement agent satisfies: D50 particle size is 0.3μm ~ 3.8μm, D10 particle size is 0.1μm ~ 1.9μm, and D90 particle size is 1.3μm ~ 6.4μm. The D50 particle size, D10 particle size, and D90 particle size are obtained by testing with a laser particle size distribution instrument, the D50 particle size indicates the particle size corresponding to when the cumulative volume distribution percentage of the lithium supplement agent reaches 50%, the D10 particle size indicates the particle size corresponding to when the cumulative volume distribution percentage of the lithium supplement agent reaches 10%, and the D90 particle size indicates the particle size corresponding to when the cumulative volume distribution percentage of the lithium supplement agent reaches 90%.

[0079] For example, the D50 particle size can be 0.3 μm, 0.5 μm, 0.7 μm, 0.8 μm, 1.0 μm, 1.5 μm, 1.7 μm, 1.9 μm, 2.0 μm, 2.2 μm, 2.4 μm, 2.5 μm, 2.7 μm, 2.9 μm, 3.0 μm, 3.1 μm, 3.5 μm or 3.9 μm, and the D10 particle size can be 0.1 μm, 0.2 μm, 0.3 μm, 0.5 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.3 μm, The particle size of D90 can be 1.5μm, 1.6μm, 1.7μm or 1.9μm, etc., and the particle size of D90 can be 1.3μm, 1.4μm, 1.5μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm, 2.5μm, 2.9μm, 3.0μm, 3.2μm, 3.5μm, 3.6μm, 3.8μm, 4.0μm, 4.2μm, 4.8μm, 4.9μm, 5.0μm, 5.2μm, 5.5μm, 5.8μm, 6.0μm, 6.3μm or 6.4μm, etc.

[0080] Since the D50 particle size of the lithium supplement agent is 0.3μm ~3.8μm, the D10 particle size is 0.1μm ~1.9μm, and the D90 particle size is 1.3μm ~6.4μm, the particle size distribution of the lithium supplement agent is concentrated and the particle size is small, which is beneficial to effectively reduce the granularity during the coating process when applied to the positive electrode sheet, thereby improving the flatness of the positive electrode sheet.

[0081] In some embodiments, the tap density of the lithium supplement agent is 1.43 g / mL to 1.59 g / mL, and / or, the compacted density of the lithium supplement agent is 2.48 g / mL to 2.76 g / mL, and / or, the specific surface area of ​​the lithium supplement agent is 3.47 m 2 / g~4.79 m 2 / g.

[0082] For example, the tap density of the lithium supplement may be 1.43 g / mL, 1.45 g / mL, 1.46 g / mL, 1.48 g / mL, 1.5 g / mL, 1.52 g / mL, 1.53 g / mL, 1.55 g / mL, 1.56 g / mL, 1.57 g / mL or 1.59 g / mL, etc.

[0083] The compacted density of the lithium supplement agent can be 2.48 g / mL, 2.50 g / mL, 2.52 g / mL, 2.55 g / mL, 2.58 g / mL, 2.60 g / mL, 2.62 g / mL, 2.64 g / mL, 2.65 g / mL, 2.67 g / mL, 2.68 g / mL, 2.70 g / mL, 2.71 g / mL, 2.73 g / mL, 2.74 g / mL, 2.75 g / mL or 2.76 g / mL, etc.

[0084] The specific surface area of ​​the lithium supplement can be 3.47 m 2 / g, 3.48m 2 / g, 3.49m 2 / g, 3.50 m 2 / g, 3.52 m 2 / g, 3.54 m 2 / g, 3.57 m 2 / g, 3.58 m 2 / g, 3.59 m 2 / g, 3.60 m 2 / g, 3.63 m 2 / g, 3.65 m 2 / g, 3.68 m 2 / g, 3.67 m 2 / g, 3.68 m 2 / g, 3.71 m 2 / g, 3.72 m 2 / g, 3.73 m 2 / g, 3.75 m 2 / g, 3.78 m 2 / g, 3.82 m 2 / g, 3.85 m 2 / g, 3.88 m 2 / g, 3.89 m 2 / g, 3.92 m 2 / g, 3.94 m 2 / g, 3.96 m 2 / g, 3.97 m 2 / g, 4.01 m2 / g, 4.02 m 2 / g, 4.05 m 2 / g, 4.08 m 2 / g, 4.09 m 2 / g, 4.13 m 2 / g, 4.15 m 2 / g, 4.18 m 2 / g, 4.19 m 2 / g, 4.25 m 2 / g, 4.26 m 2 / g, 4.28 m 2 / g, 4.30 m 2 / g, 4.33 m 2 / g, 4.35 m 2 / g, 4.38 m 2 / g, 4.40 m 2 / g, 4.45 m 2 / g, 4.49 m 2 / g, 4.52 m 2 / g, 4.57 m 2 / g, 4.59 m 2 / g, 4.63 m 2 / g, 4.65 m 2 / g, 4.69 m 2 / g, 4.72 m 2 / g, 4.75 m 2 / g, 4.78 m 2 / g or 4.79 m 2 / g, etc.

[0085] Controlling the tap density and compaction density of the lithium supplement agent within the above tap density and compaction density is beneficial to effectively improving the energy density of the lithium supplement agent; controlling the specific surface area of ​​the lithium supplement agent within the above range is beneficial for the lithium supplement agent to have a suitable contact area with the electrolyte when used in secondary batteries, thereby giving full play to the lithium supplement effect.

[0086] In some embodiments, the mass proportion of iron in the lithium supplement is 3.47% to 5.49%, the mass proportion of boron is 0.46% to 1.26%, the mass proportion of lithium in the lithium supplement is 12.78% to 13.99%, and the mass proportion of phosphorus in the lithium supplement is 30.98% to 31.98%. For example, the mass proportion of iron in the lithium supplement can be 3.47%, 3.49%, 3.52%, 3.54%, 3.55%, 3.62%, 3.67%, 3.70%, 3.72%, 3.75%, 3.79%, 3.81%, 3.83%, 3.85%, 3.89%, 3.92%, 3.94%, 3.96%, 3.98%, 4.0%, 4.05%, 4.08%, 4.1%, 4.15%, 4.18%, 4.20%, 4.30%, 4.40%, 4.50%, 4.60%, 4.70%, 4.80%, 4.90 ...91%, 4.92%, 4.93%, 4.94%, 4.95%, 4.96%, 4.97%, 4.98%, 4.99%, 4.10%, 4.11%, 4.12%, 4.13%, 4.14%, 4.15%, 4.16%, 4.17%, 4.18%, 4.19%, 4.29%, 4.30%, 4.31%, 4.32%, 4.3 %, 4.2%, 4.25%, 4.3%, 4.36%, 4.38%, 4.4%, 4.42%, 4.45%, 4.47%, 4.49%, 4.5%, 4.53%, 4.55%, 4.58%, 4.59%, 4.6%, 4.63%, 4.67%, 4.69%, 4.71%, 4.73%, 4.75%, 4.78%, 4.8%, 4.83%, 4.85%, 4.89%, 4.91%, 4. 95%, 4.97%, 4.99%, 5.02%, 5.06%, 5.08%, 5.09%, 5.12%, 5.14%, 5.18%, 5.19%, 5.23%, 5.25%, 5.28%, 5.29%, 5.33%, 5.36%, 5.38%, 5.39%, 5.4%, 5.42%, 5.43%, 5.45%, 5.47% or 5.49%, etc., and the mass proportion of boron can be 0.46%, 0 .5%, 0.51%, 0.53%, 0.55%, 0.58%, 0.6%, 0.61%, 0.63%, 0.64%, 0.67%, 0.69%, 0.7%, 0.75%, 0.79%, 0.82%, 0.86%, 0.89%, 0.93%, 0.95%, 0.96%, 0.98%, 1%, 1.1%, 1.15%, 1.16%, 1.19%, 1.22%, 1.25% or 1.26%, etc.

[0087] The coating layer of the lithium supplement agent has high electrical conductivity, which is beneficial to improving the electrical conductivity of the lithium supplement agent.

[0088] In some embodiments, the water content in the lithium supplement is less than 205ppm, and / or the chloride ion content in the lithium supplement is less than 90ppm, and / or the metaborate content in the lithium supplement is less than 70ppm, and / or the residual carbonate content in the lithium supplement is less than 680ppm. Further, the water content in the lithium supplement is 101ppm~204ppm; the chloride ion content in the lithium supplement is 17ppm~87ppm; the metaborate content in the lithium supplement is 35ppm~69ppm; and the residual carbonate content in the lithium supplement is 512ppm~678ppm. For example, the water content in the lithium supplement may be 200ppm, 190ppm, 189ppm, 185ppm, 182ppm, 180ppm, 175ppm, 172ppm, 170ppm, 168ppm, 165ppm, 160ppm, 158ppm, 155ppm, 152ppm, 149ppm, 147ppm, 145ppm, 140ppm, 135ppm, 130ppm, 128ppm, 125ppm, 123ppm, 120ppm, 115ppm, 110ppm, 108ppm, 105ppm or 101ppm, etc.; the chloride ion content in the lithium supplement may be 80ppm, 78ppm75ppm, 70ppm, 60ppm, 56ppm m, 52ppm, 50ppm, 45ppm, 42ppm, 40ppm, 35ppm or 30ppm, etc.; the content of metaborate in the lithium supplement agent can be 69ppm, 65ppm, 60ppm, 50ppm, 40ppm, 32ppm, 30ppm, 29ppm, 25ppm or 20ppm, etc.; the residual carbonate content of the lithium supplement agent can be 678ppm, 675ppm, 670ppm663ppm, 660ppm, 658ppm, 655ppm, 650ppm, 648ppm, 643ppm, 641ppm, 639ppm, 620ppm, 610ppm, 590ppm, 569ppm, 557ppm, 520ppm, 503ppm or 512ppm, etc.

[0089] By controlling the contents of the above-mentioned moisture, chloride ions, metaborate and / or carbonate, etc. within the above-mentioned respective ranges, the effects of moisture, chloride ions, metaborate and / or carbonate on the lithium supplement agent can be reduced, the stability of the lithium supplement agent can be improved, and the generation of by-products can be reduced, which is beneficial to improving the lithium supplement effect and further improving the capacity, safety and stability of the secondary battery having the lithium supplement agent.

[0090] In some embodiments, the powder resistivity of the lithium supplement is less than 1.0 Ω.cm. Further, the powder resistivity of the lithium supplement may be 0.3 Ω.cm to 0.9 Ω.cm. For example, the powder resistivity of the lithium supplement may be 0.9 Ω.cm, 0.7 Ω.cm, 0.67 Ω.cm, 0.5 Ω.cm, 0.4 Ω.cm or 0.3 Ω.cm, etc.

[0091] The lithium supplement has good electrical conductivity. When applied to the positive electrode, it can not only play the role of lithium supplement, but also act as a conductive agent, thereby improving the performance of the secondary battery.

[0092] In some embodiments, under the conditions of 25°C and 8% humidity, the first charge specific capacity of the lithium supplement at a rate of 0.05C is 512 mAh / g ~518 mAh / g, preferably 514 mAh / g ~518 mAh / g; under the conditions of 25°C and 8% humidity, the first discharge specific capacity of the lithium supplement at a rate of 0.05C is 86.1 mAh / g ~89.5 mAh / g.

[0093] For example, under the conditions of 25°C and 8% humidity, the first charge specific capacity of the lithium supplement at a rate of 0.05C can be 513 mAh / g, 514 mAh / g, 516 mAh / g or 518 mAh / g, etc., and the first discharge specific capacity of the lithium supplement at a rate of 0.05C can be 87 mAh / g, 89 mAh / g or 89.5 mAh / g, etc.

[0094] The lithium supplement agent has a relatively high initial charge specific capacity and initial discharge specific capacity, and has a significant lithium supplement effect.

[0095] In some embodiments, the lithium supplement has good stability when applied to the positive electrode of a secondary battery. Specifically, after being placed in air at a temperature of 25°C and a humidity of 70% for 1 hour, the lithium supplement has a first charge capacity of 507 mAh / g to 510.1 mAh / g at a rate of 0.05C, preferably 509 mAh / g to 510.1 mAh / g; the first discharge capacity is 82.6 mAh / g to 86.7 mAh / g;

[0096] After being placed in air at 25°C and 70% humidity for 4 hours, the lithium supplement has a first charge capacity of 504 mAh / g to 505 mAh / g at a rate of 0.05C, and a first discharge capacity of 80 mAh / g to 83.2 mAh / g.

[0097] After being placed in air at 25°C and 70% humidity for 24 hours, the lithium supplement has a first charge capacity of 500 mAh / g to 502 mAh / g at a rate of 0.05C, and a first discharge capacity of 77 mAh / g to 81.5 mAh / g.

[0098] After being placed in air at a temperature of 25°C and a humidity of 70% for 48 hours, the lithium supplement had a first charge capacity of 488 mAh / g ~501.2 mAh / g at a rate of 0.05C, and a first discharge capacity of 75 mAh / g ~81.3 mAh / g.

[0099] For example, after being placed in air at a temperature of 25°C and a humidity of 70% for 1 hour, the lithium supplement agent may have a first charge specific capacity of 508 mAh / g, 509 mAh / g or 510.1 mAh / g at a rate of 0.05C, etc.; after being placed in air at a temperature of 25°C and a humidity of 70% for 1 hour, the lithium supplement agent may have a first discharge specific capacity of 83 mAh / g, 84 mAh / g, 85 mAh / g, 86 mAh / g at a rate of 0.05C, etc.

[0100] For example, after being placed in air at a temperature of 25°C and a humidity of 70% for 4 hours, the lithium supplement may have a first charge capacity of 504.5 mAh / g, 504.8 mAh / g, etc. at a rate of 0.05C; after being placed in air at a temperature of 25°C and a humidity of 70% for 4 hours, the lithium supplement may have a first discharge capacity of 81 mAh / g, 82 mAh / g, 82.5 mAh / g or 83.2 mAh / g, etc. at a rate of 0.05C.

[0101] For example, after being placed in air at a temperature of 25°C and a humidity of 70% for 24 hours, the lithium supplement agent may have a first charge specific capacity of 500.5 mAh / g, 501 mAh / g, 501.5 mAh / g or 502 mAh / g at a rate of 0.05C; after being placed in air at a temperature of 25°C and a humidity of 70% for 24 hours, the lithium supplement agent may have a first discharge specific capacity of 77.5 mAh / g, 79 mAh / g or 81 mAh / g at a rate of 0.05C.

[0102] For example, after being placed in air at a temperature of 25°C and a humidity of 70% for 48 hours, the lithium supplement agent may have a first charge specific capacity of 490 mAh / g, 491 mAh / g, 492 mAh / g, 493 mAh / g, 494 mAh / g, 495 mAh / g, 498 mAh / g or 501.2 mAh / g, etc. at a rate of 0.05C; after being placed in air at a temperature of 25°C and a humidity of 70% for 48 hours, the lithium supplement agent may have a first discharge specific capacity of 75.1 mAh / g, 76 mAh / g, 77 mAh / g, 79 mAh / g, 80.7 mAh / g or 81 mAh / g, etc. at a rate of 0.05C.

[0103] In some embodiments, the above-mentioned first charge specific capacity and first discharge specific capacity of the lithium supplement agent are obtained by preparing a positive electrode sheet having the lithium supplement agent, assembling the positive electrode sheet into a button battery and conducting testing.

[0104] In some embodiments, the positive electrode plate includes a positive electrode active material, a binder and a conductive agent. The positive electrode active material is a lithium supplement as described above. The binder is preferably PVDF (polyvinylidene fluoride), and other adhesive materials suitable for positive electrode plates can also be used. The conductive agent is preferably a carbon conductive material, such as conductive carbon black (SP) and the like. The above-mentioned positive electrode active material, binder, and conductive agent are proportioned in a suitable mass ratio, and an aluminum sheet is used as a current collector to prepare a positive electrode plate. The mass ratio of the positive electrode active material, binder, and conductive agent can be 85:8:7.

[0105] In a second aspect, the present application provides a method for preparing a lithium supplement, such as Figure 1 As shown, including:

[0106] S11, providing a first slurry, wherein the first slurry includes lithium phosphite;

[0107] S12, mixing the first slurry with sodium borohydride and ferrous chloride, and subjecting the mixture to a first reaction treatment to obtain a crude product;

[0108] S13, filtering, washing and drying the crude product to obtain the lithium supplement agent;

[0109] The lithium supplement comprises lithium phosphite and a coating layer coated on the surface of the lithium phosphite, and the material of the coating layer comprises iron boride.

[0110] The method for preparing the lithium supplement provided in the embodiments of the present application can be used to prepare the lithium supplement as described above.

[0111] In some embodiments, lithium phosphite can be obtained through commercial channels or can be made by self-production, which is not specifically limited here.

[0112] After preparing the first slurry, the first slurry is mixed with sodium borohydride and ferrous chloride, and the sodium borohydride and ferrous chloride react to form ferric boride. The specific reaction equation is shown in the following (4), thereby obtaining a coating layer coated on the surface of lithium phosphite, and the material of the coating layer is ferric boride. The preparation method is simple, and the raw materials are convenient and easy to obtain. Compared with the lithium supplement material with high lithium capacity in the related art, the raw materials of the lithium supplement agent are cheap and the preparation cost is low.

[0113] NaBH4+FeCl2→ FeB+NaCl+H2+HCl Formula (4)

[0114] In some embodiments, S11, providing a first slurry, wherein the first slurry includes lithium phosphite, comprises:

[0115] obtaining a first solution of phosphorous acid, wherein the solvent of the first solution comprises at least one of methanol, ethanol, glycerol, propanol and propylene glycol;

[0116] Adding lithium salt to the first phosphorous acid solution, performing a second reaction treatment, and obtaining a first reaction slurry;

[0117] The first reaction slurry is ground until the lithium phosphite in the first reaction slurry reaches a preset particle size to obtain a first slurry.

[0118] The first reaction slurry is obtained by adding a lithium salt to a first solution of phosphorous acid, and then crystallizing lithium phosphite from the first solution by a second reaction treatment and utilizing the low solubility of lithium phosphite in the above solvent. The first reaction slurry is then ground to a preset particle size to obtain the first slurry. The use of phosphorous acid as a raw material is conducive to keeping the first slurry acidic, so that when the first reaction treatment is subsequently carried out, the first reaction treatment is kept under acidic conditions, which is conducive to the generation of iron boride, which is chemically plated on the surface of the lithium phosphite to form a coating layer.

[0119] In some embodiments, the molar ratio of the phosphorous acid, sodium borohydride and ferrous chloride is 1: (0.05-0.1): (0.025-0.05). The molar ratio of sodium borohydride and ferrous chloride is controlled within the above range, so that the first reaction treatment is carried out under acidic conditions and an excess of sodium borohydride, which is conducive to the reaction of sodium borohydride and ferrous chloride and the formation of a coating layer of suitable thickness on the surface of lithium phosphite.

[0120] For example, the amount ratio of the phosphorous acid, sodium borohydride and ferrous chloride can be 1:0.05:0.025, 1:0.07:0.025, 1:0.08:0.025, 1:0.08:0.025, 1:0.09:0.025, 1:0.1:0.025, 1:0.05:0.03, 1:0.05:0.04, 1:0.05:0.05, 1:0.06:0.03, 1:0.07:0.03, 1:0.08:0.03, 1:0.1:0.03, 1:0.06:0.04, 1:0.06:0.05, 1:0.07:0.04, 1:0.07:0.05, 1:0.08:0.04, 1:0.08:0.05, 1:0.09:0.04, 1:0.09:0.05, 1:0.1:0.04 or 1:0.1:0.05, etc.

[0121] In some embodiments, the temperature of the second reaction treatment is 35° C. to 55° C., and the time of the second reaction treatment is 0.5 h to 1 h. By controlling the temperature and time of the second reaction treatment within the above range, the reaction of the lithium salt and phosphorous acid to generate lithium phosphite is facilitated to proceed fully.

[0122] For example, the temperature of the second reaction treatment can be 35°C, 38°C, 39°C, 40°C, 42°C, 45°C, 46°C, 48°C, 50°C, 52°C, 53°C or 55°C, etc., and the time of the second reaction treatment can be 0.5h, 0.7h, 0.8h, 0.9h or 1h.

[0123] In some embodiments, the lithium salt comprises at least one of lithium carbonate, lithium sulfite and lithium bicarbonate. The lithium salt reacts with phosphorous acid to generate lithium phosphite and gas, thereby reducing the introduction of impurities while preparing lithium phosphite.

[0124] Wherein, lithium carbonate and lithium sulfite can be added in solid form, and lithium bicarbonate can be added in solution form.

[0125] In some embodiments, the preset particle size is 0.3 μm to 3 μm. The preset particle size can be the D50 particle size of lithium phosphite, which is in the range of 0.3 μm to 3 μm, which is conducive to obtaining lithium phosphite with a concentrated particle size distribution and a small particle size, thereby facilitating the coating of the coating layer and obtaining a lithium supplement with a concentrated particle size distribution and a small particle size.

[0126] For example, the preset particle size may be 0.5 μm, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, 2.1 μm, 2.2 μm, 2.5 μm, 2.8 μm, etc.

[0127] In some embodiments, the lithium salt is selected from lithium carbonate. When the lithium salt is selected from lithium carbonate, the gas generated by the reaction of lithium carbonate and phosphorous acid is carbon dioxide, which reduces the generation of irritating gas compared to sulfur dioxide.

[0128] In some embodiments, the molar ratio of lithium element in the lithium salt to phosphorous acid is (1.8-1.9):1, so that the phosphorous acid is appropriately excessive, which is beneficial to maintaining acidic conditions and facilitating the first reaction treatment under acidic conditions to obtain iron boride.

[0129] For example, the molar ratio of lithium element in the lithium salt to phosphorous acid may be 1.8:1, 1.82:1, 1.84:1, 1.86:1, 1.88:1 or 1.9:1, etc.

[0130] When the lithium salt is selected from at least one of lithium carbonate and lithium sulfite, the molar ratio of the lithium salt to the phosphorous acid is (0.9-0.95):1.

[0131] In some embodiments, when the solvent of the first solution is selected from methanol, the first solution of phosphorous acid can be a methanol solution of phosphorous acid.

[0132] In some embodiments, the step of obtaining the first reaction slurry may be:

[0133] The lithium salt is added to the first solution of phosphorous acid under stirring, and the reaction is carried out at a temperature of 35°C to 55°C for 0.5h to 1h until no bubbles are generated, that is, the reaction is completed to obtain the first reaction slurry. The reaction equation is shown in the following formula (5).

[0134] H3PO3+Li2CO3→Li2HPO3+H2O+CO2↑ Formula (5)

[0135] In some embodiments, the mass fraction of phosphorous acid in the first phosphorous acid solution may be 5% to 10%. For example, the concentration of the first phosphorous acid solution may be 5%, 6%, 7%, 8%, 9% or 10%, etc.

[0136] In some embodiments, the first reaction slurry may be ground by ball milling to obtain a first slurry containing lithium phosphite having a preset particle size.

[0137] In some embodiments, when the first reaction slurry is ground by ball milling, ceramic balls may be added for grinding. The diameter of the ceramic balls may be 0.3 mm to 0.8 mm.

[0138] In some embodiments, S12, the step of mixing the first slurry of sodium borohydride and ferrous chloride and subjecting the mixture to a first reaction treatment to obtain a crude product comprises:

[0139] After mixing a solution containing sodium borohydride, a solution containing ferrous chloride and the first slurry, a crude product is obtained at a first reaction temperature and after a first preset time.

[0140] In these embodiments, by mixing a solution containing sodium borohydride and a solution containing ferrous chloride with the first slurry, the product generated by the reaction of sodium borohydride and ferrous chloride can be used to uniformly coat the lithium phosphite, which helps to improve the uniformity of the coating layer.

[0141] In some embodiments, the mixing may be performed under first stirring at a speed of 100 r / min to 300 r / min, so as to improve the uniformity of mixing of the first slurry with the solution containing sodium borohydride and the solution containing ferrous chloride.

[0142] In some embodiments, the mixing temperature may be 25°C to 45°C, for example, 26°C, 30°C, 35°C, 40°C, etc.

[0143] In some embodiments, the mixing time is 60 min to 120 min, so as to fully mix the first slurry with the solution containing sodium borohydride and the solution containing ferrous chloride.

[0144] In some embodiments, the solution containing sodium borohydride, the solution containing ferrous chloride and the first slurry are mixed, and then the solution containing sodium borohydride and the solution containing ferrous chloride are mixed together and then transported to the first slurry and then mixed with the first slurry, or the solution containing sodium borohydride and the solution containing ferrous chloride are transported to the first slurry and then mixed with the first slurry. It should be noted that when the solution containing sodium borohydride and the solution containing ferrous chloride are mixed first and then transported to the first slurry and then mixed with the first slurry, the above-mentioned mixing time, temperature during mixing, and the first stirring speed during mixing are the mixing time and stirring speed when the solution containing sodium borohydride and the solution containing ferrous chloride are mixed and mixed with the first slurry.

[0145] In some embodiments, the mass fraction of sodium borohydride in the solution containing sodium borohydride can be 3% to 8%, and the mass fraction of ferrous chloride in the solution containing ferrous chloride can be 5% to 10%. For example, the mass fraction of sodium borohydride in the solution containing sodium borohydride can be 3%, 4%, 5%, 6%, 7% or 8%, etc., and the mass fraction of ferrous chloride in the solution containing ferrous chloride can be 5%, 6%, 7%, 8%, 9% or 10%, etc.

[0146] In some embodiments, the first reaction temperature is 25°C to 45°C, for example, 26°C, 30°C, 35°C, 40°C, etc.

[0147] In this embodiment, by controlling the first reaction temperature to be 25° C. to 45° C., it is beneficial to fully generate iron boride, and further beneficial to form a coating layer with a suitable thickness and coverage rate on the surface of lithium phosphite.

[0148] In some embodiments, the temperature during mixing can be the same as the first reaction temperature.

[0149] In some embodiments, the first preset time is 30 min to 60 min, for example, 35 min, 40 min, 45 min, 50 min, 55 min, etc., which is conducive to the sufficient generation of iron boride and improves the coverage rate of the coating layer on the surface of lithium phosphite.

[0150] Furthermore, the solvent used in the solution containing sodium borohydride and the solvent used in the solution containing ferrous chloride are independently selected from at least one of methanol, ethanol, glycerol, propanol and propylene glycol, that is, they can be the same as the solvent used in the first solution.

[0151] For example, when the first solution of lithium phosphite is a methanol solution of lithium phosphite, the solution containing sodium borohydride may be a methanol solution of sodium borohydride, and the solution containing ferrous chloride may be a methanol solution of ferrous chloride.

[0152] In some embodiments, after the solution containing sodium borohydride and the solution containing ferrous chloride are mixed with the first slurry, a second stirring is performed at the first reaction temperature and within the first preset time, which is beneficial to the full reaction of sodium borohydride and ferrous chloride.

[0153] In some embodiments, the second stirring speed may be 100 r / min to 300 r / min.

[0154] In some embodiments, the speed of the first agitation is the same as the speed of the second agitation.

[0155] In some embodiments, in S13, the lithium phosphite forming the coating layer can be washed with the same solvent as the first solution, and the mother liquor after washing and the mother liquor collected by filtration can be recovered by distillation for reuse.

[0156] For example, when the solvent used in the first solution is methanol, the lithium phosphite forming the coating layer can be washed with methanol, which is beneficial to reduce the residual moisture in the lithium phosphite forming the coating layer during the washing process, thereby minimizing the introduction of moisture into the lithium supplement.

[0157] In some embodiments, the above drying can be performed under vacuum, that is, the above drying process can be vacuum drying. The vacuum degree of the drying process can be -0.09Mpa~-0.07Mpa, and the temperature of the drying process can be 80℃~100℃, which is conducive to more effective removal of water and reduction of residual moisture. For example, the vacuum degree of the drying process can be -0.09Mpa, -0.08Mpa or -0.07Mpa, etc., and the temperature of the drying process can be 80℃, 85℃, 90℃, 95℃ or 100℃, etc.

[0158] In some embodiments, when the above-mentioned drying process is carried out under vacuum, a protective gas may be first used to replace the gas in the vacuum chamber until the oxygen content in the vacuum chamber is less than 500 ppm, and then the vacuum is evacuated to a vacuum degree of -0.09 MPa to -0.07 MPa, which is beneficial to further reduce the oxygen content during drying, thereby further improving the material stability of the lithium supplement and reducing the generation of by-products such as lithium phosphate.

[0159] For example, the protective gas may include nitrogen, argon and / or helium.

[0160] In some embodiments, during the drying process, the drying is terminated when the moisture content is less than 0.1% by mass, so as to reduce the moisture in the lithium supplement and improve the stability of the lithium supplement.

[0161] In some embodiments, the preparation method may further include: after drying is completed, screening, electromagnetic iron removal and packaging of the material, so as to obtain a lithium supplement having a particle size, impurity content, etc. that meet the requirements, thereby achieving effective lithium supplementation.

[0162] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a current collector, and a positive electrode material disposed on at least one side of the current collector along its thickness direction, wherein the positive electrode material comprises the lithium supplement as described in the first aspect.

[0163] In the positive electrode plate provided in the embodiment of the present application, the positive electrode plate contains the above-mentioned lithium supplement agent, which adopts a coating layer having iron boride and is coated on the surface of lithium phosphite. It has improved safety performance, stability, conductivity and lithium supplement effect and low cost, thereby improving the safety, stability, conductivity and lithium supplement effect of the positive electrode plate and reducing the cost of the positive electrode plate, and is beneficial to increasing the capacity of the battery when applied to the battery.

[0164] In a fourth aspect, an embodiment of the present application provides a secondary battery, including a positive electrode sheet, a negative electrode sheet and a separator;

[0165] Wherein, the positive electrode plate is the positive electrode plate as described in the third aspect.

[0166] In the secondary battery provided in the embodiment of the present application, since the secondary battery includes the above-mentioned positive electrode plate, it has improved safety performance, stable performance and capacity, and reduces the preparation cost.

[0167] In a fifth aspect, an embodiment of the present application provides an electrical device, which includes a plurality of batteries connected in series and / or in parallel, and at least one battery is a secondary battery as described in the fourth aspect.

[0168] In the electrical device provided in the embodiment of the present application, since the secondary battery has good stability and safety performance, low cost, can effectively replenish lithium, and has a high capacity, the electrical device has good stability and safety performance and reduced preparation cost.

[0169] The electric device provided in the embodiment of the present application may be, but is not limited to, a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.

[0170] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0171] Example 1

[0172] The preparation method of the lithium supplement provided in Example 1 is as follows:

[0173] Add methanol to phosphorous acid to obtain a clarified methanol solution (i.e., the first solution) with a phosphorous acid concentration (by mass fraction) of 8%, then add lithium carbonate (lithium salt) under stirring, the molar ratio of lithium salt to phosphorous acid is 0.93:1, react at 45°C for 1 hour, react until no bubbles are generated, and obtain a first reaction slurry, put the first reaction slurry into a ball mill for grinding, add ceramic balls with a diameter of 0.6 mm, and grind until the particle size of lithium phosphite is 2.12 μm (preset particle size), and obtain a first slurry; use methanol as a solvent to prepare a solution containing sodium borohydride and a solution containing ferrous chloride, the mass fraction of sodium borohydride in the solution containing sodium borohydride is 6%, and the mass fraction of ferrous chloride is 2.12 μm. The mass fraction of ferrous iron in the solution containing ferrous chloride is 8%. The solution containing sodium borohydride and the solution containing ferrous chloride are transported to the first slurry through a peristaltic pump for mixing. The ratio of the amount of phosphorous acid, sodium borohydride and ferrous chloride is 1:0.08:0.038. The stirring speed of the mixture is 200r / min, the mixing time is 90min, and the mixing temperature is 35°C. After the mixing is completed, the mixture is stirred at a speed of 200r / min and 35°C for 50min to obtain a crude product. After the crude product is filtered, washed and dried, the obtained material is screened, electromagnetically deironed and vacuum packaged to obtain lithium phosphite (lithium supplement) coated with iron boride. The washing is performed with methanol, and the methanol after washing and the filtered mother liquor are distilled and recovered for recycling. When the washed material is dried, nitrogen is first filled into the vacuum drying oven to make the oxygen content inside the vacuum drying oven less than 500ppm, and then vacuum is drawn. The drying temperature is 90℃, and the vacuum degree is -0.085MPa. After drying until the moisture content (by mass fraction) of the material is less than 0.1%, it is cooled to a material temperature of 40℃, and then taken out for screening, electromagnetic iron removal and vacuum packaging.

[0174] The test data of the lithium supplement agent finally obtained are shown in Table 1 below:

[0175] Table 1

[0176]

[0177] Example 2

[0178] The preparation method of the lithium supplement provided in Example 2 is as follows:

[0179] Add methanol to phosphorous acid to obtain a clarified methanol solution (i.e., the first solution) with a concentration (by mass fraction) of 5% phosphorous acid, then add lithium carbonate (lithium salt) under stirring, the molar ratio of lithium salt to phosphorous acid is 0.90:1, react at 35°C for 0.8h, react until no bubbles are generated, and obtain a first reaction slurry, put the first reaction slurry into a ball mill for grinding, add ceramic balls with a diameter of 0.3mm, grind until the particle size of lithium phosphite is 3μm (preset particle size), and obtain a first slurry; use methanol as a solvent to prepare a solution containing sodium borohydride and a solution containing ferrous chloride, the mass fraction of sodium borohydride in the solution containing sodium borohydride is 8%, and the mass fraction of ferrous chloride is 1.5%. The mass fraction of ferrous iron in the solution containing ferrous chloride is 3%. The solution containing sodium borohydride and the solution containing ferrous chloride are transported to the first slurry through a peristaltic pump for mixing. The ratio of the amount of phosphorous acid, sodium borohydride and ferrous chloride is 1:0.1:0.025. The stirring speed of the mixture is 300r / min, the mixing time is 60min, and the mixing temperature is 25°C. After the mixing is completed, the mixture is stirred at a speed of 300r / min and 25°C for 30min to obtain a crude product. After the crude product is filtered, washed and dried, the obtained material is screened, electromagnetically deironed and vacuum packaged to obtain lithium phosphite (lithium supplement) coated with iron boride. The washing is performed with methanol, and the methanol after washing and the filtered mother liquor are distilled and recovered for recycling. When the washed material is dried, nitrogen is first filled into the vacuum drying oven to make the oxygen content inside the vacuum drying oven less than 500ppm, and then vacuum is drawn. The drying temperature is 80℃, and the vacuum degree is -0.07MPa. After drying until the moisture content (by mass fraction) of the material is less than 0.1%, it is cooled to a material temperature of 40℃, and then taken out for screening, electromagnetic iron removal and vacuum packaging.

[0180] The test data of the lithium supplement agent finally obtained are shown in Table 2 below:

[0181] Table 2

[0182]

[0183] Example 3

[0184] The preparation method of the lithium supplement provided in Example 3 is as follows:

[0185] Add methanol to phosphorous acid to obtain a clarified methanol solution (i.e., the first solution) with a concentration (by mass fraction) of 10% phosphorous acid, then add lithium carbonate (lithium salt) under stirring, the molar ratio of lithium salt to phosphite is 0.95:1, react at 55°C for 0.5h, react until no bubbles are generated, and obtain a first reaction slurry, put the first reaction slurry into a ball mill for grinding, add ceramic balls with a diameter of 0.8mm, grind until the particle size of lithium phosphite is 0.3μm (preset particle size), and obtain a first slurry; use methanol as a solvent to prepare a solution containing sodium borohydride and a solution containing ferrous chloride, the mass fraction of sodium borohydride in the solution containing sodium borohydride is 3%, and the mass fraction of ferrous chloride is 2.5%. The mass fraction of ferrous chloride in the solution containing ferrous chloride is 5%. The solution containing sodium borohydride and the solution containing ferrous chloride are transported to the first slurry through a peristaltic pump for mixing. The ratio of the amount of phosphorous acid, sodium borohydride and ferrous chloride is 1:0.05:0.05. The stirring speed of the mixing is 100r / min, the mixing time is 120min, and the mixing temperature is 45°C. After the mixing is completed, the stirring reaction is continued at a speed of 200r / min and 45°C for 60min to obtain a crude product. After the crude product is filtered, washed and dried, the obtained material is screened, electromagnetically deironed and vacuum packaged to obtain lithium phosphite (lithium supplement) coated with iron boride. Washing is performed with methanol, and the methanol after washing and the filtered mother liquor are distilled and recovered for recycling. The washed material is dried by first filling nitrogen into the vacuum drying oven to make the oxygen content inside the vacuum drying oven less than 500ppm, and then evacuating the oven. The drying temperature is 100℃, the vacuum degree is -0.09MPa, and the material is dried until the moisture content (by mass fraction) is less than 0.1%. Then it is cooled to a material temperature of 40℃, and then taken out for screening, electromagnetic iron removal and vacuum packaging.

[0186] The test data of the lithium supplement agent finally obtained are shown in Table 3 below:

[0187] Table 3

[0188]

[0189] Example 4

[0190] The preparation method of the lithium supplement provided in Example 4 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:

[0191] The lithium phosphite is ground to a particle size (predetermined particle size) of 0.1 μm.

[0192] The test data of the lithium supplement agent finally obtained are shown in Table 4 below:

[0193] Table 4

[0194]

[0195] Example 5

[0196] The preparation method of the lithium supplement provided in Example 5 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:

[0197] The lithium phosphite is ground to a particle size (preset particle size) of 3.5 μm.

[0198] The test data of the lithium supplement agent finally obtained are shown in Table 5 below:

[0199] Table 5

[0200]

[0201] Example 6

[0202] The preparation method of the lithium supplement provided in Example 6 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:

[0203] The solution containing sodium borohydride and the solution containing ferrous chloride are transported to the first slurry through a peristaltic pump for mixing, and the molar ratio of the mixed phosphorous acid, sodium borohydride and ferrous chloride is 1:0.03:0.025.

[0204] The test data of the lithium supplement agent finally obtained are shown in Table 6 below:

[0205] Table 6

[0206]

[0207] Example 7

[0208] The preparation method of the lithium supplement provided in Example 7 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:

[0209] The solution containing sodium borohydride and the solution containing ferrous chloride are transported to the first slurry through a peristaltic pump for mixing, and the ratio of the amount of phosphorous acid, sodium borohydride and ferrous chloride in the mixture is 1:0.1:0.06.

[0210] The test data of the lithium supplement agent finally obtained are shown in Table 7 below:

[0211] Table 7

[0212]

[0213] Example 8

[0214] The preparation method of the lithium supplement provided in Example 8 is substantially the same as the preparation method of the lithium supplement provided in Example 1, except that:

[0215] The solution containing sodium borohydride and the solution containing ferrous chloride are transported to the first slurry through a peristaltic pump for mixing, and the molar ratio of the mixed phosphorous acid, sodium borohydride and ferrous chloride is 1:0.03:0.06.

[0216] The test data of the lithium supplement agent finally obtained are shown in Table 8 below:

[0217] Table 8

[0218]

[0219] Comparative Example 1

[0220] Comparative Example 1 provides a method for preparing a lithium-rich lithium iron oxide lithium supplement:

[0221] Red iron oxide and lithium oxide are mixed so that the molar ratio of iron to lithium in the mixture is 1:5.25, and then the mixture is calcined at 750°C for 6 hours under nitrogen protection, and then discharged after being cooled to a material temperature of 135°C, and transported to a pulverizer by positive pressure nitrogen with a humidity of 5%, and pulverized by nitrogen with a temperature of 120°C and a humidity of 2%, the dew point of the nitrogen being -20°C, and pulverized to a particle size of 2.7 μm to obtain a lithium-rich lithium ferrate lithium supplement.

[0222] The test data of the lithium supplement agent finally obtained are shown in Table 9 below:

[0223] Table 9

[0224]

[0225] Comparative Example 2

[0226] The preparation method of the lithium supplement provided in Comparative Example 2 is as follows:

[0227] Phosphorous acid is added with methanol to obtain a clarified methanol solution (i.e., a first solution) with a phosphorous acid concentration (by mass fraction) of 8%, and then lithium carbonate (lithium salt) is added under stirring, the molar ratio of lithium salt to phosphorous acid is 0.93:1, and the mixture is reacted at 45°C for 1 hour until no bubbles are generated to obtain a first reaction slurry, the first reaction slurry is put into a ball mill for grinding, ceramic balls with a diameter of 0.6 mm are added, and the mixture is ground until the particle size (preset particle size) of lithium phosphite is 2.12 μm to obtain a first slurry; methanol is used for washing, and the washed material is dried, and nitrogen is first filled into a vacuum drying oven to make the internal oxygen content less than 500 ppm, and then vacuumed, the drying temperature is 90°C, the vacuum degree is -0.085 MPa, the material is dried until the moisture content (by mass fraction) of the material is less than 0.1%, and then cooled to a material temperature of 40°C, and then taken out for screening, electromagnetic iron removal and vacuum packaging to obtain uncoated lithium phosphite (lithium supplement).

[0228] Test methods and test results

[0229] 1. The lithium supplement provided in Example 1 was characterized by scanning electron microscopy. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the particle size distribution of the lithium supplement is relatively uniform, and the particles are spherical.

[0230] 2. Chemical composition and physical and chemical index testing of lithium supplements

[0231] The lithium supplements provided in Examples 1 to 8 and Comparative Example 1 were tested for chemical composition indexes and physicochemical indexes, and the specific test results are shown in Tables 1 to 9, respectively.

[0232] Among them, in the chemical composition index test, the Fe content was determined by potentiometric titration, the phosphorus content was determined by quinoline phosphomolybdic acid weighing method, the lithium, sodium, potassium, calcium, magnesium, chromium, copper and zinc contents were determined by inductively coupled plasma atomic emission spectrometry, the chloride ion was determined by potentiometric titration, the metaborate was determined by titration, and the carbonate was determined by potentiometric titration.

[0233] In the physical and chemical index test, the moisture content in the lithium supplement is measured by Karl Fischer (KF) method; the specific surface area of ​​the lithium supplement can be measured by BET specific surface area method, such as nitrogen adsorption multi-point BET method; the powder resistivity is measured by four-probe method at a pressure of 10Mpa; the sphericity directly affects its fluidity and stacking properties. The sphericity of the lithium supplement can be measured by combining microscopic measurement method and image processing technology. The particle image is processed and analyzed by image analysis software to obtain the particle size and particle shape information of each particle, and then the particle size and particle shape information of each particle are statistically analyzed to obtain the particle size (D50) and particle size distribution, average major diameter and aspect ratio distribution, average circularity and circularity distribution and other results. Here, the average circularity is used to represent the sphericity of the lithium supplement.

[0234] In addition, the measurement method of the tap density is: using a tap density meter for testing, with the vibration number being 5000 times.

[0235] The compaction density is measured by using a compaction density meter with a test pressure of 3T and a compaction time of 30S.

[0236] It can be seen from Tables 1 to 9 that the lithium supplements provided in Examples 1 to 8 provided in the present application all contain iron and boron elements, and the mass proportion of iron can reach 3.47% to 5.49%, and the mass proportion of boron can reach 0.46% to 1.26%, indicating that the lithium supplements provided in Examples 1 to 8 form a coating layer of iron boride material on the surface of lithium phosphite.

[0237] 3. The particle size distribution of the lithium supplement provided in Examples 1 to 8 and Comparative Examples 1 to 2 was tested using a laser particle size analyzer. The particle size distribution curve of Example 1 is as follows: Figure 3 As shown, the particle size distribution results of the lithium supplement agents of Example 1 to Example 8 and Comparative Example 1 to Comparative Example 2 are shown in Table 10 below.

[0238] The thickness of the coating layer is measured by transmission electron microscopy. The coating rate of the coating layer is defined as the percentage of the coverage area of ​​the coating layer on the surface of the particle (i.e., the lithium iron oxide core of the above-mentioned embodiments 1 to 10) to the total surface area of ​​the particle. The coating amount of the coating layer is measured by diffuse reflectance infrared Fourier transform spectroscopy. The coating rate can be calculated based on the coating amount and the cross-sectional area (also called cross-sectional area) of the coating layer. The calculation formula is: , where n represents the coating rate, M represents the coating amount, q represents the molecular weight of the coating material, and NA is a constant (6.023×10 23 ), a0 represents the cross-sectional area of ​​the coating layer, S w The coating thickness and coating ratio of Examples 1 to 8 are shown in Table 10.

[0239] Table 10

[0240]

[0241] In the above Table 10, the D50 particle size represents the particle size corresponding to when the cumulative volume distribution percentage of the lithium supplement reaches 50%, the D10 particle size represents the particle size corresponding to when the cumulative volume distribution percentage of the lithium supplement reaches 10%, and the D90 particle size represents the particle size corresponding to when the cumulative volume distribution percentage of the lithium supplement reaches 90%.

[0242] It can be seen from Table 10 above that, compared with the lithium supplement provided in Comparative Examples 1 and 2, the lithium supplement provided in Examples 1 to 8 of the present application has a concentrated particle size distribution and a smaller particle size, which is beneficial to effectively avoid the generation of granularity during the coating process of the positive electrode material and improve the flatness of the electrode sheet.

[0243] 4. Electrical performance index test of lithium supplement

[0244] (1) The lithium supplement provided by Examples 1 to 8 and Comparative Examples 1 to 2 were respectively used as positive electrode active materials, mixed with conductive carbon black (SP) and PVDF in a mass ratio of 85:7:8, then added with NMP for homogenization, then coated on aluminum foil, and then dried and roller pressed. The compaction density was 2.1 g / mL, the electrolyte was 1 mol / L lithium hexafluorophosphate, and the electrolyte used ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a volume ratio of 1:1:1 as organic solvents. The negative electrode was a lithium sheet. The batteries were assembled into button cells for testing.

[0245] The button batteries prepared with the lithium supplement provided in Examples 1 to 8 were tested for the first charge specific capacity and the first discharge specific capacity at a rate of 0.05C at 25°C, 8% humidity and a voltage of 2.0V to 4.0V. The button batteries prepared with the lithium supplement provided in Comparative Example 1 were tested for the first charge specific capacity and the first discharge specific capacity at a rate of 0.05C at 2.0V to 4.5V and 2.0V to 4.0V, respectively. The button batteries prepared with the lithium supplement provided in Comparative Example 2 were tested for the first charge specific capacity and the first discharge specific capacity at a rate of 0.05C at 2.0V to 4.0V. The results are shown in Table 11 below:

[0246] Table 11

[0247]

[0248] It can be seen from Table 11 that the button batteries prepared with the lithium supplement provided by Examples 1 to 8 have a higher first charge specific capacity under the condition of a voltage of 2.0 V to 4.0 V, compared with the button batteries prepared with the lithium supplement provided by Comparative Examples 1 to 2. Specifically, the button batteries prepared with the lithium supplement provided by Examples 1 to 8 have a first charge specific capacity of 501 mAh / g to 520 mAh / g at a voltage of 2.0 V to 4.0 V at a rate of 0.05C, and a first discharge specific capacity of 81 mAh / g to 90 mAh / g at a rate of 0.05C.

[0249] From the first charge specific capacity and the first discharge specific capacity of the button batteries prepared with the lithium supplement provided in Examples 1 to 8 and the button batteries prepared with the lithium supplement provided in Comparative Example 1, it can be seen that in the same charge-discharge range (2.0V~4.0V), the button batteries prepared with the lithium supplement provided in the examples of the present application have higher charge specific capacity and discharge specific capacity, indicating that the lithium supplement provided in the examples of the present application has a lower operating voltage than lithium-rich lithium ferrite, and is more suitable for application in the positive electrode of a secondary battery.

[0250] By comparing the first charge specific capacity and the first discharge specific capacity of the button batteries prepared by the lithium supplement provided in Examples 1 to 8 and the button batteries prepared by the lithium supplement provided in Comparative Example 2, it can be seen that the first charge specific capacity of the button batteries prepared by the lithium supplement provided in Examples 1 to 8 under the condition of 0.05C rate is significantly higher than the first charge specific capacity of the button batteries prepared by the lithium supplement provided in Comparative Example 2 under the condition of 0.05C rate, which shows that after the lithium supplement provided in Examples 1 to 8 of the present application forms a coating layer on the surface of lithium phosphite, the lithium phosphite is not easy to contact with the external environment, which is beneficial to avoid the oxidation of phosphite to phosphate, reduce the formation of "dead lithium", and improve the lithium supplement effect. At the same time, the material of the coating layer has strong stability and good conductivity, thereby further improving the conductivity and material stability of the lithium supplement, and further improving the lithium supplement effect.

[0251] (2) The lithium supplements provided in Examples 1 to 8 and Comparative Examples 1 to 2 were placed in air (temperature of 25° C., humidity of 70%) for 1 h, 4 h, 24 h and 48 h, respectively, and finally assembled into button batteries according to the above (1) and tested. The test results are shown in Table 12 below.

[0252] Table 12

[0253]

[0254] It can be seen from Table 12 that, under the conditions of temperature of 25°C and humidity of 70%, the button batteries prepared with the lithium supplement provided in Examples 1 to 8 have a change degree of the first charge specific capacity and the first discharge specific capacity as the storage time increases, which is significantly smaller than the change degree of the first charge specific capacity and the first discharge specific capacity of the button batteries prepared with the lithium supplement provided in Comparative Examples 1 to 2, indicating that the lithium supplement provided in Examples 1 to 8 of the present application effectively improves the capacity and stability of the lithium supplement by forming a coating layer having iron boride on the surface of lithium phosphite, and can better meet the actual application needs.

[0255] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A lithium supplement, characterized in that: include: Lithium phosphite and a coating layer coated on the surface of the lithium phosphite; Wherein, the material of the coating layer includes iron boride.

2. The lithium supplement according to claim 1, characterized in that: The coating layer has a thickness of 0.6 μm to 2 μm, and / or a coating rate of the coating layer is greater than or equal to 93%.

3. The lithium supplement according to claim 1, characterized in that: The lithium supplement is spherical, and the sphericity of the lithium supplement is 0.81-0.87; and / or, The particle size distribution of the lithium supplement agent satisfies: D50 particle size is 0.3 μm ~ 3.8 μm, D10 particle size is 0.1 μm ~ 1.9 μm, and D90 particle size is 1.3 μm ~ 6.4 μm.

4. The lithium supplement according to claim 1, characterized in that: The tap density of the lithium supplement agent is 1.43 g / mL to 1.59 g / mL; and / or, the compacted density of the lithium supplement agent is 2.48 g / mL to 2.76 g / mL, and / or, the specific surface area of ​​the lithium supplement agent is 3.47 m 2 / g~4.79 m 2 / g.

5. A method for preparing a lithium supplement, characterized in that: include: providing a first slurry, wherein the first slurry includes lithium phosphite; The first slurry is mixed with sodium borohydride and ferrous chloride, and subjected to a first reaction treatment to obtain a crude product; The crude product is filtered, washed and dried to obtain the lithium supplement agent; Wherein, the lithium supplement comprises lithium phosphite and a coating layer coated on the surface of the lithium phosphite, and the material of the coating layer comprises iron boride.

6. The method for preparing a lithium supplement according to claim 5, characterized in that: The step of providing a first slurry, wherein the first slurry includes lithium phosphite, comprises: obtaining a first solution of phosphorous acid, wherein the solvent of the first solution comprises at least one of methanol, ethanol, glycerol, propanol and propylene glycol; Adding lithium salt to the first phosphorous acid solution, and subjecting the solution to a second reaction to obtain a first reaction slurry; Grinding the first reaction slurry until the lithium phosphite in the first reaction slurry reaches a preset particle size to obtain the first slurry; The molar ratio of the phosphorous acid, the sodium borohydride and the ferrous chloride is 1:(0.05-0.1):(0.025-0.05); and / or, The temperature of the second reaction treatment is 35°C to 55°C, and the time of the second reaction treatment is 0.5 h to 1 h; and / or, The lithium salt comprises: at least one of lithium carbonate, lithium sulfite and lithium bicarbonate; and / or, The molar ratio of the lithium element in the lithium salt to the phosphorous acid is (1.8-1.9):1; and / or, The preset particle size is 0.3 μm to 3 μm.

7. The method for preparing a lithium supplement according to claim 6, characterized in that: The first slurry is mixed with sodium borohydride and ferrous chloride, and subjected to a first reaction treatment to obtain a crude product, comprising: After mixing the solution containing the sodium borohydride and the solution containing the ferrous chloride with the first slurry, the crude product is obtained at a first reaction temperature and after a first preset time; The mixing time is 60 min to 120 min, and the mixing temperature is 25° C. to 45° C.; and / or, The first reaction temperature is 25°C to 45°C; and / or, The first preset time is 30 min~60 min.

8. The method for preparing a lithium supplement according to any one of claims 5 to 7, characterized in that: The temperature of the drying process is 80° C. to 100° C., and the vacuum degree of the drying process is -0.09 MPa to -0.07 MPa.

9. A positive electrode sheet, characterized in that: It comprises a current collector and a positive electrode material arranged on at least one side of the current collector along the thickness direction thereof, wherein the positive electrode material comprises the lithium supplement agent according to any one of claims 1 to 4 or the lithium supplement agent prepared by the preparation method of the lithium supplement agent according to any one of claims 5 to 8.

10. A secondary battery, characterized in that: Including positive electrode sheet, negative electrode sheet and separator; Wherein, the positive electrode sheet is selected from the positive electrode sheet as described in claim 9.

Citation Information

Cited By

  • Lithium supplement agent and preparation method thereof, positive plate, lithium ion battery, battery pack and electric equipment

    CN120497343A